Labour and Christianity in the mission : African workers in Tanganyika and Zanzibar, 1864-1926 - Liebst, Michelle (Religion in transforming Africa, 2021)
Important and broadening study of the way Africans engaged with missions, not as beneficiaries of humanitarian philanthropy, but as workers.